2022
DOI: 10.1055/a-1721-4908
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Neonatal Cord Blood SARS-CoV-2 Antibodies after COVID-19 Vaccination in Pregnancy: A Prospective Cohort Study

Abstract: Introduction Maternally derived antibodies are a key element of neonatal immunity. So far, limited data has shown transplacental transmission of antibodies after coronavirus disease 2019 (COVID-19) vaccination with BNT162b2 in the third trimester. Our aim was to detect vertically transferred immunity after COVID-19 vaccination with BNT162b2 (Comirnaty, BioNTech-Pfizer) or mRNA-1273 (Spikevax, Moderna) in the first, second or third trimester of pregnancy, and investigate the impact of maternal charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
1
8
0
2
Order By: Relevance
“…They concluded that “receiving both vaccine doses before delivery and longer latency from vaccination to delivery was associated with a higher IgG concentration in infants and stronger immunity” [ 52 ]. This result was also confirmed in other studies [ 86 , 87 ]. Prabhu et al studied 122 pregnant women, of whom 55 and 67 had received their first and second mRNA vaccine doses, respectively, before delivery.…”
Section: Covid-19 Vaccination and Transplacental Transfer Of Antibodiessupporting
confidence: 92%
“…They concluded that “receiving both vaccine doses before delivery and longer latency from vaccination to delivery was associated with a higher IgG concentration in infants and stronger immunity” [ 52 ]. This result was also confirmed in other studies [ 86 , 87 ]. Prabhu et al studied 122 pregnant women, of whom 55 and 67 had received their first and second mRNA vaccine doses, respectively, before delivery.…”
Section: Covid-19 Vaccination and Transplacental Transfer Of Antibodiessupporting
confidence: 92%
“…Mithal L et al [ 32 ] collected a series of cases involving 27 pregnant women; 64% received BNT162b2, 18% received mRNA-1273, and 4% received another type of vaccination without making comparisons between the different schemes because the sample of patients was small. Sourouni M et al [ 33 ], in their study of 70 vaccinated pregnant women, 89% with BNT16b2 and 10% with mRNA-1273, showed that there was no correlation between antibody levels and the week of gestation at which vaccination was performed, the time interval between birth and vaccination, maternal age, or the mother’s body mass index. Like Sourouni M et al, we found, in our study using the generalized linear model, that significance was seen in the number of vaccine doses administered rather than the maternal age, type of vaccine regimen, and history of positivity for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It should be emphasized that these two previous studies were published at the beginning of 2020, at a time when less was known about COVID-19, the disease characteristics, the course of disease and the approval of vaccines could not yet be estimated. We now know that the transplacental infection of the fetus is rather a rare event and that the vaccination of pregnant women is classified as safe 31 32 33 . In addition, the prevalence of a SARS-CoV-2 infection in the context of a pregnancy was low during the study period 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Zulassung von Impfstoffen noch nicht eingeschätzt werden konnte. Mittlerweile ist bekannt, dass die transplazentare Infektion des Fetus eher selten ist und die Impfung schwangerer Frauen wird als sicher eingestuft 31 32 33 . Zudem war die Prävalenz einer SARS-CoV-2-Infektion im Rahmen einer Schwangerschaft im Untersuchungszeitraum gering 34 .…”
Section: Diskussionunclassified
See 1 more Smart Citation